FACILITATION CIVIL AVIATION FORMALITIES AS A STRATEGIC GOAL TO IMPROVE GLOBAL SECURITY - Chulinda, Liudmyla; Popov, Roman (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the study is the effectiveness of ICAO measures to simplify standards and recommended practices, the need for their implementation in the national legislation of member states. It requires an analysis of the issues of civil aviation priorities regarding the protection of personal data, the collection and processing of the necessary information. Research methods: comparative and systematic methods were used, in particular, to clarify the essence and effectiveness of ICAO standards in Annex 9 «Facilitation of Formalities» in accordance with Article 14 of the Convention on International Civil Aviation. Results: it was found that the development of modern technologies contributes to the fact that most social and economic activities take place on the Internet, so privacy and protection of personal data are becoming increasingly important. The state’s activities in the field of air transport include compliance with requirements related to the issuance of travel documents, information exchange and identification of high-risk travelers, security screening of people and cargo, and the fight against terrorism. Discussion: the ICAO Facilitation program provides Contracting States with the means to maximize the efficiency of border formalities, as well as to achieve and maintain a high level of security and effective law enforcement. Ensuring the reliability and timeliness of the implementation of civil aviation facilitation rules results in the recognition and implementation of generally recognized values enshrined in international civil aviation documents of universal and regional significance. In particular, such updating and expansion is taking place due to the implementation of international and European civil aviation standards into the legal system of Ukraine.